2006
DOI: 10.1038/sj.npp.1301060
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Ginkgo biloba EGb761 Facilitates Extinction of Conditioned Fear Measured by Fear-Potentiated Startle

Abstract: A standard extract of Ginkgo biloba (EGb761) has been used in the treatment of various common geriatric complaints including vertigo, short-term memory loss, hearing loss, lack of attention, or vigilance. We demonstrated that acute systemic administration of EGb761 facilitated the acquisition of conditioned fear. Many studies suggest the neural mechanism underlies extinction is similar to the acquisition. This raises a possibility that EGb761 may modulate and accelerate the fear extinction process. We tested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…We found that EGb761 can enhance fear memory formation rather than serve as an anti-stress buffer . In addition, we also demonstrated that either systemic or intra-amygdaloid administration of EGb761 facilitate conditioned fear extinction in a dose-dependent manner (Yang et al 2007b).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…We found that EGb761 can enhance fear memory formation rather than serve as an anti-stress buffer . In addition, we also demonstrated that either systemic or intra-amygdaloid administration of EGb761 facilitate conditioned fear extinction in a dose-dependent manner (Yang et al 2007b).…”
Section: Introductionmentioning
confidence: 65%
“…2a). The doses of EGb761 chosen were based on our previous studies (Yang et al 2007b). ACSF and EGb761 were infused into the BLA 10 min prior to fear conditioning.…”
Section: Experiments 2: Effects Of Intra-amygdaloid Infusion Of Egb761mentioning
confidence: 99%
“…To check if ERK is involved in SNL-induced NR2B phosphorylation, MEK inhibitor PD98059 (0.1 μg each site) [44] was injected into bilateral NAc shell at day 7 after SNL. pNR2B expression was significantly reduced by PD98059 1 h after injection (Fig.…”
Section: Snl Increases Pnr2b Expression Via Ccr2 In the Nacmentioning
confidence: 99%
“…Более суще-ственное снижение балла по эмоциональной шкале не было статистически достоверным, однако выявленная тенденция может свидетельствовать о влиянии танакана на эмоцио-нальное состояние пациентов с головокружением. Посколь-ку предположение о способности EGb 761 уменьшать трево-гу выдвигалось и в других исследованиях, как клинических, так и экспериментальных [18,19], целесообразны дальней-шие исследования, оценивающие способность танакана улучшать эмоциональное состояние пациентов, страдающих острыми и хроническими вестибулярными расстройствами. Возможный анксиолитический эффект танакана может быть очень важен в лечении таких пациентов, поскольку тес-ная взаимосвязь вестибулярных нарушений с эмоциональ-ными расстройствами хорошо известна [20][21][22].…”
Section: рис 1 выраженность головокружения по шог в процессе вестибunclassified